REFLEKSI PENDIDIKAN NILAI BANGSA KITA - Triyanto, Agus (Paradigma, 2015)
discussion in this article starts from the emergence of a variety of problems and global issues such as violation of human rights, multi-cultural-ethnic-religious reality, life environment, world peace, violence phenomena, and drug abuse which indispensably make educational practitioners think about an appropriate educational system capable of facing challenges. Therefore, an educational system focusing on moral value internalization emphasizing the aspect of universal humanism is important. Such a system should be adjusted to our needs in order for us as a nation to be able to face every challenge. The past education was deemed to fail to create people capable of individualizing and participating. As a result, our educational outputs are not only poor in skill and intellectual capacity but also fragile in character and morality. A national problem arising is not only unemployment and alumni’s poor capability but also a threat of moral decadence and criminality. The fact that the reform euphoria brings about effects on all aspects of the nation’s life, initially directed towards substantial matters, shows that it still needs a long struggle to attain the reform objective. In fact, our nation needs not only characters with morality but also those with intellect, capable of thinking clearly and profoundly, idealistic and realistic, and having a long-term vision. Those with intellect are able to see the invisible, to see what is behind an emergent phenomenon, and to raise appropriate critical questions. Not all people are able to see a variety of moral problems that are usually behind emergent phenomena. The conclusion of this article is that to prevent moral values prevalent in society from extinction, the society itself has to transfer them to the next generation. A way to do so is education. Through education, the society teaches knowledge, concepts of live, norms, and attitudes in social life, and teaches how to behave in social life, nation life, and government life. Key words : nation, value education, character, moral